A pulse-burst laser system for Thomson scattering on NSTX-U. (10th October 2017) - Hartog, D.J. Den; Borchardt, M.T.; Holly, D.J.; Diallo, A.; LeBlanc, B.
Abstract: A pulse-burst laser system has been built for Thomson scattering on NSTX-U, and is currently being integrated into the NSTX-U Thomson scattering diagnostic system. The laser will be operated in three distinct modes. The base mode is continuous 30 Hz rep rate, and is the standard operating mode of the laser. The base mode will be interrupted to produce a "slow burst" (specified 1 kHz rep rate for 50 ms) or a "fast burst" (specified 10 kHz rep rate for 5 ms). The combination of base mode → → interruption → → burst mode is new and has not been implemented on any previous pulse-burst laser system. Laser pulsing is halted for a set period (1 ∼ 1 minute) following a burst to allow the YAG rods to cool; this type of operation is called a heat-capacity laser. The laser is Nd:YAG operated at 1064 nm, q q -switched to produce⩾ 1.5 J pulses with20 ∼ 20 ns FWHM. It is flashlamp pumped, with dual-rod oscillator (9 mm) and dual-rod amplifier (12 mm). Variable pulsewidth drive of the flashlamps is accomplished by IGBT (insulated gate bipolar transistor) switching of electrolytic capacitor banks. Direct control of the laser Pockels cell drive enables optimal pulse energy extraction. The laser system has demonstrated compliance with all specifications, and is capable of exceeding design specifications by significant margins, e.g., higher rep rates for longer burst periods. Burst operation of this laser system will be used to capture fast time evolution of the electron temperature and density profiles during events such as ELMs, the L-H transition, and various MHD modes.